Research Trends about Analogy Studies in Science Education: A Descriptive Content Analysis - Kübra Sezer; Faik Özgür Karataş (Journal of Science Learning, 2022)
Analogies are bridges between prior knowledge and new knowledge to make meaning of the new one. Analogies are particularly effective in teaching science concepts that are not very apparent in the students' everyday lives due to their abstract nature. For this reason, it is essential to adapt analogies to teach new concepts effectively in science education. Analogy-related studies published between 2009 and 2020 were examined in this manuscript to determine the use of analogies as a teaching technique in science education (Physics, Chemistry, Biology). To reach the studies about "Analogy," ERIC, EBSCO, Springer LINK, Taylor Francis, Wiley Online Library Full Collection, Science Direct, ProQuest Dissertations, Theses Global, Google Scholar, and Scopus databases were searched. Then, Turkish databases, including ULAKBIM and YÖK (National Thesis Center), were also searched. A total of 80 research papers published between 2009 and 2020 that met the study's criteria were examined. Within the scope of the study, the subject areas, purpose, sample, results, and suggestions of compiled analogy studies were focused on. Based on the analysis, it was determined that most of the analogy research was conducted in the field of chemistry, the most employed methodology was qualitative research, and the most common purpose of these studies was to see the effects on academic achievement. When the studies were conducted to examine academic achievement, it was seen that the use of analogy applications as a teaching technique in science teaching has positive results on student achievement.